Information, Contracting, and Quality Costs - Baiman, Stanley; Fischer, Paul E.; Rajan, Madhav V. (Management Science, 2000)
This article analyzes the relation between product quality, the cost of quality, and the information that can be contracted upon. We consider a setting where a risk neutral supplier sells an intermediate product to a risk neutral buyer. The supplier incurs prevention costs to reduce the probability of selling a defective product, and the buyer incurs appraisal costs to identify defects. Both decisions are subject to moral hazard. We show that the first-best outcome can be obtained if either: (i) the supplier's prevention decision is contractible; or (ii) the buyer's appraisal decision and either internal failure (i.e., the product's failing the buyer's appraisal test) or external failure (i.e., the product's failing after being sold by the buyer) are contractible events; or (iii) both internal and external failure are contractible events. We then focus on the second-best setting where actions and failures are not contractible and study the effect of making the buyer's appraisal result contractible. Relative to first-best, if a buyer's return decision is contractible (but not his appraisal result), the supplier incurs lower prevention costs, the buyer incurs higher appraisal costs, expected internal failure costs are higher, and the total cost of quality is higher. The expected costs of external failure, however, may actually be lower relative to first-best. We then show that installing an information system that makes the appraisal result contractible reduces the inefficiency associated with the seller's prevention activity, increases the inefficiency associated with the buyer's quality appraisal activity, and unambiguously improves product quality.